Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/mpr.1513
|View full text |Cite
|
Sign up to set email alerts
|

Estimated probability of becoming a case of drug dependence in relation to duration of drug-taking experience: a functional analysis approach

Abstract: Measured as elapsed time from first use to dependence syndrome onset, the estimated ‘induction interval’ for cocaine is thought to be short relative to the cannabis interval, but little is known about risk of becoming dependent during first months after onset of use. Virtually all published estimates for this facet of drug dependence epidemiology are from life histories elicited years after first use. To improve estimation, we turn to new month-wise data from nationally representative samples of newly incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…With regard to medication utilization, consistent with existing literature, 7,13 we found that polypharmacy was highly associated with increased risk of PRTF admission. Moreover, post discharge polypharmacy prescribing practices persisted.…”
Section: Discussionsupporting
confidence: 90%
“…With regard to medication utilization, consistent with existing literature, 7,13 we found that polypharmacy was highly associated with increased risk of PRTF admission. Moreover, post discharge polypharmacy prescribing practices persisted.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the cross-sectional nature of the data cannot inform the direction of the relationship between cannabis/tobacco exposure and associated symptoms. Future longitudinal research that asks newly incident substance users to give month-by-month reports of frequency of use and occurrence of clinical features might help to avoid these inherent limitations of cross-sectional data (Vsevolozhskaya and Anthony, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For many years, progress in the field of treating cannabis dependence was retarded by a widespread belief that ‘cannabis dependence’ syndromes did not exist. This belief continues to be challenged by emerging evidence on the coherence of the dependence syndrome and related conditions such as ‘cannabis use disorder’, the biological plausibility of these conditions, and their clinical implications [7785]. Early forms of cannabis dependence treatment were introduced, as described in a review article by Budney and colleagues [86], published more than a decade ago.…”
Section: The Five Main Rubrics Of Epidemiology As Applied To Cannabismentioning
confidence: 99%